Judicial Policy and Societal Implications: Marriage Dispensation Rejections in Pangkalan Bun's Religious Court - Jumrotunisak; Soeradji, Elvi; Hidayati, Tri (Journal of Education and Religious Studies, 2025)
This study examines the complex interplay of legal, religious, and social factors influencing the rejection of marriage dispensation requests in Pangkalan Bun's Religious Court. Through in-depth interviews and document analysis, the study explores the court's decision-making process, the prevailing societal norms, and the broader societal implications of these rejections. Findings reveal that the court's decisions are shaped by a combination of legal precedents, religious interpretations, and social pressures. Individuals denied dispensations often face stigma, economic hardship, and mental health challenges. At the community level, these rejections can lead to increased social conflict, weakened social cohesion, and changes in family structures. The study highlights the urgent need for comprehensive measures to address the multifaceted consequences of rejecting marriage dispensations, including strengthening education, improving access to support services, and promoting gender equality.